QUALITY IMPROVEMENT FOR MATERNAL AND CHILD HEALTH IN PRIMARY HEALTH CARE: A SCOPING REVIEW - Tarigan, Dhea Benedikta; Dhamanti, Inge (Journal of Public Health Research and Community Health Development, 2023)
ABSTRACT Background: Primary Health Care (PHC) is a gatekeeper in providing comprehensive services for maternal and child health (MCH). MCH services in PHC remain limited and have not been entirely handled and distributed. Based on this, MCH in PHC requires Quality Improvement (QI) interventions. Purpose: Identify the implementation of QI in maternal and child health in PHC and identify the most QI tools or approaches used. Methods: This is a scoping review of the qualitative and quantitative results of studies that focused on Quality Improvement for maternal and child health in Primary Health Care. The inclusion criteria consist of articles published in English and original articles; the topic is an improvement for maternal and child health in Primary Health Care; full text and open access.  Results: Six findings have been found, which are: QI interventions for MCH problems mostly happen in Low Middle Income Countries (LMIC); Plan-Do-Study-Act (PDSA)  was the most used QI intervention approach; the success of QI implementation including the interventions; the most used QI Intervention; the role of stakeholders; and factors related to the successes of QI intervention.  Conclusion: Implementation QI is often carried out in Low-Middle Income Countries (LMIC).  Furthermore, various QI interventions have been used to solve maternal and child health issues. The most used QI tool was PDSA. Training, mentoring, and workshops for midwives and clinic teams were most often QI interventions implemented.